The Relationship of The Judicial Commission with the Ideal Supreme Court - Markoni Markoni (Journal Research of Social Science, Economics, and Management, 2022)
Relationship is a matter of the occurrence of cause and effect. The ideal relationship is something that is aspired or coveted or desired by every individual, group and body or organization who wants to establish a relationship based on the interests and desires of both parties, Same is the case with the Judicial Commission and the Supreme Court. In the dynamics of an organization that differences are a means to give birth to solutions in creating togetherness and establishing ideal relationships in building a common concept and rules. The research methodology used in this paper uses the Normative Empirical research method, which aims to answer what factors influence the relationship between the Judicial Commission and the Supreme Court, as well as how to improve the ideal relationship between the Judicial Commission and the Supreme Court.